Predation on Leptinopterus Hope species (Coleoptera, Lucanidae) by three species of Reduviidae (Hemiptera, Heteroptera) in the Atlantic Forest, Brazil - Grossi, Paschoal Coelho; Koike, Ricardo Mitsuhiro; Gil-Santana, Hélcio Reinaldo (EntomoBrasilis, 2012)
The natural occurrence of predation on Leptinopterus burmeisteri Arrow and Leptinopterus femoratus (Olivier) (Coleoptera, Lucanidae, Lucaninae) by Zelurus angularis (Stål) (Reduviinae), Apiomerus mutabilis Costa Lima, Seabra & Hathaway and Apiomerus nigricollis Stål (Apiomerinae) (Hemiptera, Reduviidae), in the state of São Paulo, Brazil, is recorded. Additional data on the predatory habits of A. nigricollis are also presented here. Predação de Espécies de Leptinopterus Hope (Coleoptera, Lucanidae) por Três Espécies de Reduviidae (Hemiptera, Heteroptera) na Floresta Atlântica, Brasil Resumo. Relata-se a ocorrência de predação natural de Leptinopterus burmeisteri Arrow e Leptinopterus femoratus (Olivier) (Coleoptera, Lucanidae, Lucaninae) por Zelurus angularis (Stål) (Reduviinae), Apiomerus mutabilis Costa Lima, Seabra & Hathaway e Apiomerus nigricollis Stål (Apiomerinae) (Hemiptera, Reduviidae) no Estado de São Paulo, Brasil. Dados adicionais sobre hábitos predadores de A. nigricollis são apresentados também.